Elemental composition of two ecologically contrasting seamount fishes, the bluemouth (Helicolenus dactylopterus) and blackspot seabream (Pagellus bogaraveo). Issue 1 (15th November 2015) - Raimundo, Joana; Vale, Carlos; Martins, Inês; Fontes, Jorge; Graça, Gonçalo; Caetano, Miguel
Abstract: Concentrations of V, Cr, Mn, Co, Ni, Cu, Zn, As, Se, Cd and Pb were determined in muscle, liver and gonads of two ecologically contrasting fishes, Helicolenus dactylopterus (benthic) and Pagellus bogaraveo (benthopelagic). Elevated concentrations of As, Se and Cd found in tissues of both species appear to mirror the contribution of volcanic activity to the natural inputs of elements to Azorean waters. Results showed different element accumulation between the two species. Whereas higher concentrations were found in the liver of P. bogaraveo, elevated values were observed in the muscle of H. dactylopterus . Differences in accumulation are most likely related to metabolic rates, diet specificities and habitat. Concentrations in gonads varied up to four orders of magnitude, being higher and more variable in P. bogaraveo than H. dactylopterus . Elevated values of Cd were detected in gonads of both species despite its non-essential role on metabolic functions, presumably related to elimination. Graphical abstract: Highlights: Different partitioning of trace elements between benthic and benthopelagic fish. Possible influence of ecological factors (e.g. metabolic rates and habitat) on partition. Elevated As, Se and Cd concentrations in H. dactylopterus and P. bogaraveo . Possible volcanic activity contributing to natural inputs to Azorean waters.